A modified method for harvesting thoracodorsal artery perforator flaps in a simple and time‐saving approach. Issue 8 (29th April 2016) - Kim, Sang Wha; Youn, Seungki; Kim, Jeong Tae; Kim, Youn Hwan
Abstract : Background: With the increasing popularity of perforator flaps in several fields of reconstructive surgery, there have been many attempts to develop safer and more efficient harvesting methods. In this article, we propose a modified method for harvesting the thoracodorsal perforator (TDAP) flap during lower extremity reconstruction, and compare it with the conventional method. Methods: Between January 2011 and December 2013, 74 TDAP flaps were used in reconstruction of lower extremity defects. The flaps included a single musculocutaneous perforator, and one artery, and one vein anastomosis were included in the study. Using the modified method for flap harvest, a reliable perforator was found and a cuff of muscle was left around the perforator without intramuscular dissection. The patient group meeting the inclusion criteria of the study comprised 20 females and 54 males ranging from 12 to 93 years of age. The conventional dissection method for harvesting the TDAP flap was used in 47 patients, the modified method in 27 patients. Flap dimensions, donor site closure, pedicle lengths, total operating times, times from skin incision to initiation of microsurgery, and complications of the two harvesting methods were compared. Results: When the modified method was used, total operating time was reduced from 311 to 272 min ( P < 0.05). There were no significant differences in postoperative complications related to the flap or the donor site between the two groups. Conclusions: The modified method of perforator dissection is relatively safe and straightforward. Using it significantly reduces the operating time. © 2015 Wiley Periodicals, Inc. Microsurgery 36:642–646, 2016.